Models of Political Communication between District Parliament and Local Government: A Case Study of the Regional Autonomy in Sumedang, West Java, Indonesia - Akadun, Akadun (SOSIOHUMANIKA, 2011)
ABSTRACT: The research is aimed to create model of political communication between DPRD (Dewan Perwakilan Rakyat Daerah or House of Representatives at Regional Level) and PEMDA (Pemerintah Daerah or Local Government) for local government boardâs performance improvement in order to the effectivity of the regional autonomy implementation at Sumedang Regency, West Java Province, Indonesia. The influence of political communication between DPRD and PEMDA for local government boardâs performance improvement in order to the effectivity of the regional autonomy implementation at Sumedang Regency is small, but it is significant. This is resulted by barrier of political communication between DPRD and PEMDA, especially difference of interest, ideology and paradigm from stakeholders, and shareholders of Sumedang Regency. Meanwhile, the influence of local government boardâs performance to the effectivity of the regional autonomy implementation at Sumedang Regency is large enough and significant. This is interrelated with job description local government board which is interconected with functions of management as critical factor in process of work.Key words: House of Representative at Regional Level, Local Government, political communication, performance, effectiveness, implementation, and regional autonomy.About the Author: Dr. Akadun is attached at the STIA (Sekolah Tinggi Ilmu Administrasi or College of Administration Science) 11 April in Sumedang, West Java, Indonesia, as a Lecturer at the KOPERTIS (Koordinator Perguruan Tinggi Swasta or Coordinator of Private Universities) IV West Java and Banten Region. He can be reached at: duniausaha2005@yahoo.co.idHow to cite this article? Akadun. (2011). âModels of Political Communication between District Parliament and Local Government: A Case Study of the Regional Autonomy in Sumedang, West Java, Indonesiaâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.4, No.1 [Mei], pp.21-32. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 1979-0112. Chronicle of article: Accepted (March 24, 2011); Revised (April 29, 2011); and Published (May 20, 2011). Â  Â